Domains of polyhedral type and boundary extensions of biholomorphisms - ZAITSEV, DMITRI (My University, 1998)
For D, D? analytic polyhedra in Cn, it is proven that a biholomorphic mapping f : D ! D? extends holomorphically to a dense boundary subset under certain condition of general position. This result is also extended to a more general class of domains with no smoothness condition on the boundary.
PUBLISHED
Keywords: Pure & Applied Mathematics